Active Second-Order Pole-Zero Cancellation Control for Speed Servo Systems With Current Sensor Fault Tolerance - Kim, Seok Kyoon; Lee, Kyo Beum (IEEE Transactions on Circuits and Systems II: Express Briefs, 2023)
This brief presents an advanced output-feedback technique for speed regulation tasks in servo systems, which reduces the system model independence and is independent of the current feedback, leading to fault tolerance. Hence, the output position error drives the model-free order reduction filter for speed, and the acceleration feedback (as a replacement for the current loop) is admissible. Furthermore, the proposed control law includes specially structured active damping terms in the feed-forward loop to actively trigger second-order pole-zero cancellation, forming a simple single-loop proportional-integral derivative-type structure with compensation terms. Finally, a 420-W prototype DC servo system experimentally validates the effectiveness of the proposed technique.
Keywords: Closed-loop system; Filter; Pole zero cancellation; Poles-zeros cancellation; Second orders; Second-order pole-zero cancelation; Sensor fault tolerance; Sensors faults; Servo-motor; Speed regulation; Tuning; filter; second-order pole-zero cancellation; sensor fault tolerance; servo motor; Speed regulation